Perancangan Aplikasi Kasir Berbasis Web untuk Transaksi Barcode pada Warung Sunda - Muhammad Irvan Eren; Afiani Agus Abdillah; Nabilah Febriana; Zakiyya Ady Putri (CV. Multi Kreasi Media, 2026)
The rapid development of information technology has encouraged businesses to adopt computerized systems to improve operational efficiency. Warung Sunda still performs sales transactions manually, causing recording errors, delays in service, and difficulties in managing sales reports. This study aims to design and implement a web-based cashier application integrated with barcode scanner technology to support transaction activities at Warung Sunda. Data collection methods included observation, interviews, and documentation. The system was developed using the Waterfall software development model. PHP was utilized as the programming language, while MySQL was employed as the database management system. The developed application provides features such as user authentication, menu management, barcode-based transaction processing, payment management, receipt printing, and sales reporting. The results indicate that the application can accelerate transaction processing, reduce data entry errors, improve data management efficiency, and enhance customer service quality. Therefore, the implementation of a web-based cashier application is expected to support more effective and efficient business operations.